A brief, patient- and proxy-reported outcome measure in advanced illness: Validity, reliability and responsiveness of the Integrated Palliative care Outcome Scale (IPOS). (September 2019) - Murtagh, Fliss EM; Ramsenthaler, Christina; Firth, Alice; Groeneveld, Esther I; Lovell, Natasha; Simon, Steffen T; Denzel, Johannes; Guo, Ping; Bernhardt, Florian; Schildmann, Eva; van Oorschot, Birgitt; Hodiamont, Farina; et al.
Background: Few measures capture the complex symptoms and concerns of those receiving palliative care. Aim: To validate the Integrated Palliative care Outcome Scale, a measure underpinned by extensive psychometric development, by evaluating its validity, reliability and responsiveness to change. Design: Concurrent, cross-cultural validation study of the Integrated Palliative care Outcome Scale – both (1) patient self-report and (2) staff proxy-report versions. We tested construct validity (factor analysis, known-group comparisons, and correlational analysis), reliability (internal consistency, agreement, and test–retest reliability), and responsiveness (through longitudinal evaluation of change). Setting/participants: In all, 376 adults receiving palliative care, and 161 clinicians, from a range of settings in the United Kingdom and Germany Results: We confirm a three-factor structure (Physical Symptoms, Emotional Symptoms and Communication/Practical Issues). Integrated Palliative care Outcome Scale shows strong ability to distinguish between clinically relevant groups; total Integrated Palliative care Outcome Scale and Integrated Palliative care Outcome Scale subscale scores were higher – reflecting more problems – in those patients with 'unstable' or 'deteriorating' versus 'stable' Phase of Illness (F = 15.1, p < 0.001). Good convergent and discriminant validity to hypothesised items and subscales of the Edmonton Symptom Assessment System and Functional Assessment of Cancer Therapy–General is demonstrated. The Integrated Palliative care Outcome Scale shows good internal consistency (α = 0.77) and acceptable to good test–retest reliability (60% of items kw  > 0.60). Longitudinal validity in form of responsiveness to change is good. Conclusion: The Integrated Palliative care Outcome Scale is a valid and reliable outcome measure, both in patient self-report and staff proxy-report versions. It can assess and monitor symptoms and concerns in advanced illness, determine the impact of healthcare interventions, and demonstrate quality of care. This represents a major step forward internationally for palliative care outcome measurement.